The Incompatability Between Formalized Approaches in Economics and Flexible Sociological Theories - Mingione, Enzo (The International Journal of Sociology of Agriculture and Food, 2021)
The following paper is a reply to Vernon Ruttan's article "The Sociology of Development and Underdevelopment: Are There Lessons in Economics'?", which is an attempt to point out the potential contributions of sociologists utilizing modernizalion theory, dependency theory and world systems theory to economics. The argument put forth in this paper is basically a partial agreement of Ruttan's comment that communication between economists and sociologists has become rare. However, the paper explains this barrier by emphasizing three points. First. that sociology has developed into a decreasingly systematic, flexible discipline. Second, it has adopted various and differing theoretical paths which co-exist as accepted epistemological modes. Three, sociology has forcefully rejected the Parsonian project to codify and systematize the discipline within a structural-functionalist approach. The conclusion made is thal inevitably, any socio-cultural explanation of variations in econoinic change is bound to disrupt the very explanatory framework proposed by economics. ResumenLa Incompatibilidad entre Ia Aproximación Formalizada en Economía y la Flexible Teoría Sociológica El siguiente comentario es una respuesta al artículo de Vernan Ruttan "La sociología del desarrollo y del subdesarrollo: ¿Lecciones para la economía?", el cual es un intento para puntualizar la potencial contribución de los sociólogos, que utilizan la teoría de la modernización, la teoría de la dependencia y la teoría del sistema mundial, a los economsítas. El argumento central de mi ponencia es básicamente un parcial acuerdo con el comentario de Ruttan de que la comunicación entre economistas y sociólogos se ha hecho a medias. No obstante, la ponencia explica estas barreras enfatizando tres puntos. Primero, que la sociología se ha desarrollado como una disciplina flexible y con una decreciente sistematización. Segundo, ésta ha adoptado variados y diferentes propuestas teóricas que coexisten como formas epistemológicas aceptadas. Tercero, la sociología ha tenido un enérgico rechazo del proyecto Parsoniano de codificar y sistematizar la disciplina bajo la aproximación funcional-estructuralista. La conclusión a que llegamos es que inevitablemente la explicación de la variación sociocultural del cambio económico está limitada por la ruptura con la muy explicativa armazón teórica propuestas por los economistas.